NATION CULTURAL RECOGNITION APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Siska Wulandari; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2008)
The growing world of computer technology so that all problems can be solved with a computer, one of which is to create "Application Introduction to Cultural Nation", where with this one can obtain information from the local culture in Indonesia and is designed with the view that considering the ease in in operation. This application can be run on a computer that is running Windows-based operating system.